2013
DOI: 10.1002/cssc.201300032
|View full text |Cite
|
Sign up to set email alerts
|

Superior Performance of Metal–Organic Frameworks over Zeolites as Solid Acid Catalysts in the Prins Reaction: Green Synthesis of Nopol

Abstract: Scheme 1. Prins reaction of b-pinene with formaldehyde.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 56 publications
3
33
0
3
Order By: Relevance
“…22 Recently, in the work of Čejka and co-workers different types of MOFs materials were used in Prins condensation of β-pinene and paraformaldehyde [32,33]. The results are somewhat in line with the current work, since strong Brønsted acid sites of zeolites BEA and FAU showed significantly lower selectivity to the target Nopol than MOFs with Lewis sites resulting in the former case in an unwanted reaction of pinene isomerization [33]. Activity was also seen to be influenced by the Lewis acidity.…”
Section: Side Reactionsmentioning
confidence: 99%
“…22 Recently, in the work of Čejka and co-workers different types of MOFs materials were used in Prins condensation of β-pinene and paraformaldehyde [32,33]. The results are somewhat in line with the current work, since strong Brønsted acid sites of zeolites BEA and FAU showed significantly lower selectivity to the target Nopol than MOFs with Lewis sites resulting in the former case in an unwanted reaction of pinene isomerization [33]. Activity was also seen to be influenced by the Lewis acidity.…”
Section: Side Reactionsmentioning
confidence: 99%
“…It is found that HPW@MIL-100(Fe) shows a high catalytic activity in the reactions conducted, suggesting the applicability of HPW@MIL-100(Fe) in the esterification. By assuming that the esterification takes place predominantly in the cages of HPW@MIL-100(Fe), the yield of the formed ester decreases when the carbon chain length in the monohydric alcohols increases, most likely due to the steric hindrance for the reaction [31]. For comparison, Amberlyst-15, a commercials resin catalyst often used in acid-catalyzed reactions [80,81], was also used in the esterification of acetic acid and n-hexanol.…”
Section: Esterificationmentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57][58][59][60][61] Acidic and basic polymers can exhibit high catalytic activity in condensation reactions like the Pechmann, 62 Knoevenagel, [63][64][65][66][67][68][69][70][71][72][73][74][75][76] and Prins reactions. 77 Coordination polymers can work as catalysts through two different components, viz. the metal ions, which either provide the coordinatively unsaturated nodes and/or form the active metal sites integrated into the linker ligand, and the ligands.…”
Section: Introductionmentioning
confidence: 99%